Fabrication and characterizations of additively manufactured PVDF-HFP composites for potential force sensing applications - Metwalli, Khaled Mohamed (2024)
Polyvinyldene fluoride (PVDF) and its copolymers have attracted considerable interest among researchers as piezoelectric materials since their discovery. Due to their satisfactory piezoelectric properties and excellent mechanical characteristics, they have found various applications, including in flexible force sensors. Researchers often reinforced the polymer matrix with fillers to enhance its performance as force sensors. However, the solvents commonly used in the mixing process were often deemed hazardous and toxic, leading to the search for an alternative. Among the potential fabrication methods, researchers have reported that using Fused Deposition Modeling (FDM) to 3D print PVDF composites has resulted in improved piezoelectric performance. In this study, a copolymer of PVDF, Polyvinyldene fluoride- hexaflouropropylene (PVDF-HFP), was reinforced and 3D printed to investigate the influence of the fillers on its piezoelectric characteristics and identify the effect of the printing parameters on its piezoelectric and mechanical properties. Initially, the pure polymer was 3D printed to investigate the effect of the printing parameters and the Design of Experiment (DOE) method was employed to optimize the printing parameters. The composite was synthesised through the solution casting of a PVDF-HFP matrix reinforced with Barium Titanate and Untreated Activated Carbon. To investigate its viability as an alternative solvent, Dimethylsulfoxide (DMSO) was selected as the solvent. The optimum mixture design of experiments (MDOE) method was employed to assist in investigating the effect of the fillers and help optimize the filler content in the matrix. The utilization of the MDOE was successful, and the formulation of 84.21 wt.% PVDF-HFP, 15.00 wt.% BTO, and 0.79 wt.% UAC predicted by the software recorded the maximum β-phase of 71.895%. It is also worth noting that DMSO was deemed a viable alternative due to the tested formulations recording β-phase content values that are comparable to values reported in literature. The DOE analysis run on the pure PVDF-HFP showed that using a higher printing temperature, lower printing speed, and thinner layer thickness resulted in a maximised β-phase content. The following information were carried forward to aid in printing the PVDF-HFP composite. It was shown that the printed composite recorded a lower force sensitivity when compared to the pure polymer despite the slightly higher β-phase. Despite limited performance, all printed samples still demonstrated piezoelectricity and were capable of detecting forces as low as 1N confirming that FDMprinted PVDF copolymer composites have potential as flexible force sensors.